Modelling biosensors with perforated membrane - Baronas, Romas; Ivanauskas, Feliksas; Kulys, Juozas (Lietuvos matematikos rinkinys, 2005)
This paper presents a two-dimensional-in-space mathematical model of amperometric biosensors with perforated membrane. The model is based on the diffusion equations containing a non-linear term related to the Michaelis–Menten kinetics of the enzymatic reaction. The digital simulation was carried out using the finite difference technique. Using computer simulation of the biosensors action, the influence of the geometry of the perforated membrane on the biosensor response was investigated.
Keywords: reaction-diffusion; mathematical modelling; biosensor; perforated membrane